Effect of Maternal and Fetal Characteristics in Feto-Placental Doppler and Impact of Using Adjusted Standards in the Definition of Fetal Growth Restriction at Term - Rial-Crestelo, Marta; Velasco-Santiago, Ana Rosy; Lubusky, Marek; Hermanova, Katerina; Kajdy, Anna; Modzelewski, Jan; Krofta, Ladislav; Vojtech, Jiri; Ferriols-Pérez, Elena; Rueda-García, Carol; Parra-Cordero, Mauro; Socias, Pamela; et al. (Fetal diagnosis and therapy, 2021)
INTRODUCTION: This study aimed to determine the effect and clinical impact of physiological characteristics on the 95th/5th centile of the umbilical artery (UA) Doppler and the cerebroplacental ratio (CPR), at 36+ weeks. METHODS: From the multicenter randomized trial "Ratio37," we selected 4,505 low-risk pregnant women between June 2016 and January 2020. We registered physiological characteristics and the pulsatility indexes (PI) of the UA and middle cerebral artery (36-39 weeks). The 95th/5th centile of the UA PI and CPR was modeled by quantile regression. To evaluate the clinical impact of adjusting Doppler, we retrospectively applied gestational age (GA) and fully adjusted standards to 682 small for gestational age (SGA)-suspected fetuses (37 weeks) from a cohort of consecutive patients obtained between January 2010 and January 2020. RESULTS: Several physiological characteristics significantly influenced the 95th/5th centile of the UA and CPR PI. The fully adjusted 95th centile of the UA was higher, and the 5th centile of the CPR was lower than GA-only-adjusted standards. Of the 682 SGA fetuses, 150 (22%) were classified as late fetal growth restricted only by GA and 112 (16.4%) when we adjusted Doppler. These 38 fetuses had similar perinatal outcome than the SGA group. DISCUSSION: The 95th/5th centile of the UA and CPR PI is significantly influenced by physiological characteristics. Adjusting Doppler standards could differentiate better between FGR and SGA.
Keywords: gestační stáří; Umbilical artery Doppler; plod; Cerebroplacental ratio; arteria cerebri media; Doppler standards; Female; novorozenec; růstová retardace plodu; Gestational Age; ženské pohlaví; ultrasonografie dopplerovská; arteriae umbilicales; Placenta; lidé; Fetus; Infant, Newborn; těhotenství; Fetal growth restriction; Ultrasonography, Prenatal; retrospektivní studie; Pulsatile Flow; Adjusted Doppler standards; Small for gestational age; Fetal Growth Retardation; Infant, Small for Gestational Age; Middle Cerebral Artery; pulzatilní průtok; Pregnancy; placenta; ultrasonografie prenatální; Ultrasonography, Doppler; Retrospective Studies; Umbilical Arteries; hypotrofický novorozenec; Humans